(untitled) (Journal Of Educational and Psychological Researches, 2011)
unacceptable social behaviors, particularly withdrawal behavior that appears in children with autism represent a major problem hindering the process of communication with those around them and therefore the process of mergence with them be difficult. The withdrawal causes a real affect deficit for children with autism limits the possibility of development of their intellectual and mental growth due to their solitude and the weakness of their focus in the acquisition of pedagogical skills and lack the necessary social skills to maintain the relations of friendship and enjoyment of them. withdrawal children fail to participate in group activities as they are reluctant to interact with others, which leads to ignoring or ill-treatment lead to increased isolation, and the cause of their failure or reluctance due to their lack of social skills in dealing and communicating with others, whether in play or talk . seeing that the importance of this subject the researcher pay attention to it. The current research aimed to: Building a tool to diagnosing the withdrawal behavior of the children with autism. Diagnosing children with withdrawal behavior of the children with autism. Application of consulting program for decreasing withdrawal behavior of the children with autism. identify the effectiveness of the program in reducing the withdrawal behavior in children with autism. And the research community of autistic present children at the Institute of Rami, their number (6) children, and at the Institute of Al-Rahman their number (10) children, males and females , and the sample research was (6) from the children with withdrawal behavior, and the number of children that have been diagnosing at Rami Institute was (4) males and (2) children male and female at Al-Rahman Institute in age from (4-6) years old , and in order to achieve the research goals ,three following main tools have been building : First: the tool of diagnosing the withdrawal behavior of the children with autism. Second : consulting program for decreasing withdrawal behavior of the children with autism. Third : the researcher using a digital camera as a developed method, to observing some behaviors and observing the extent of its development before and after the application of consulting program for decreasing withdrawal behavior of the children with autism. Therewith, data has been revised statistically by means of implementation the following methods : ((Pearson’s correlation coefficient, Mann Whitney test, chi square, Wilcookson test, keroskal test), The results showed the following : There are statistical significant differences in reducing withdrawal behavior after the implementation of consulting program between the first pre-test and the first post-test for the first post-test . There are statistical significant differences in reducing withdrawal behavior of the children with autism, between the first post-test and the second post-test for the second post-test. There are statistical significant differences in the second post-test and the final post-test for the final post-test. According to these results the researcher reached to a several of important recommendation.